Driver workload analysis using an interactive 3D driving simulator - Christodoulou, Smaragda; Michael-Grigoriou, Despina; Gregoriades, Andreas; Pampaka, Maria; Vicuna Franco, Patricio Francisco; Mouskos, Kyriacos C. (My University, 2013)
Diagnosing the causes of road accidents and the development of effective countermeasures to reduce accident rates is of key importance in road safety. Human error is one of the principal influencing factors that leads to road accidents, and is attributed to increased mental workload induced by distractions. Workload, however, is characterized by intrinsic properties that are difficult to observe. Hence, phenotype behaviours, such as lane deviations, could act as good predictors of driver workload. Driving simulators emerged as a promising technology for the analysis of driving conditions and road users‟ behaviour in an attempt to tackle the problem of road accidents. The work presented herein demonstrates the design and development of a driving simulator, using a 3D game engine that aims to contribute towards evaluating black spots in road networks by promoting rapid design of realistic models and facilitating the specification of test scenarios. The developed simulator was employed to evaluate the impact of distractors on driving behaviours of local road users for a chosen black spot in Limassol-Cyprus. Data collected from the experiments are analyzed, and the main findings in regards to the above relationships are presented and discussed.
Keywords: Driving simulator; Workload; Distractions